The private equity premium puzzle revisited: new evidence on the role of heterogeneous risk attitudes - Frank M. Fossen (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The empirical finding that entrepreneurs tend to invest a large share of their wealth in their own firms despite comparably low returns and high risk has become known as the private equity premium puzzle. This paper provides evidence supporting the hypothesis that lower risk aversion of entrepreneurs, and not necessarily credit constraints, may explain this puzzle. The analysis is based on a large, representative panel data set for Germany, which provides information on asset portfolios and experimentally validated risk attitudes. The results show that both the ownership probability and the conditional portfolio share of private business equity significantly increase with higher risk tolerance.
Keywords: G11; G32; L26; J23; D81; 330; Entrepreneurship; private equity; investment; risk aversion; Unternehmer; Anlageverhalten; Private Equity; Investition; Risikoaversion; Equity Premium Puzzle; Deutschland